2021
DOI: 10.1002/pc.25924
|View full text |Cite
|
Sign up to set email alerts
|

Coaxial electrospinning process toward optimal nanoparticle dispersion in polymeric matrix

Abstract: Nanoreinforced polymers have gained popularity in the last decades since they exhibit enhanced properties (compared to pristine polymers) that are useful in a wide range of applications. Unfortunately, dispersion of nanoparticles (NPs) into polymeric matrices is a major problem since they tend to form agglomerates, limiting the improvement of properties and further applications. In this work, we propose the use of coaxial electrospinning as one-step method to disperse NPs in a polymeric matrix. Particularly, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 34 publications
(41 reference statements)
0
9
0
Order By: Relevance
“…However, when the SiO 2 content increased to 80 mg·mL –1 , the fiber diameter began to be uneven and increased significantly (Figure S3a). This was because too much SiO 2 nanoparticles destroyed the continuity of the polymer matrix and hindered the stretching force acting on the polymer ejecting jet during electrospinning …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when the SiO 2 content increased to 80 mg·mL –1 , the fiber diameter began to be uneven and increased significantly (Figure S3a). This was because too much SiO 2 nanoparticles destroyed the continuity of the polymer matrix and hindered the stretching force acting on the polymer ejecting jet during electrospinning …”
Section: Resultsmentioning
confidence: 99%
“…This was because too much SiO 2 nanoparticles destroyed the continuity of the polymer matrix and hindered the stretching force acting on the polymer ejecting jet during electrospinning. 35 The surface Si element content of the PAN/SiO 2 −PU membranes was characterized by EDS mapping, as shown in Figure 7a−d. It can be seen that the Si element on the fiber surface increased with increasing SiO 2 content in the shell solution.…”
Section: Effect Of the Siomentioning
confidence: 99%
“…Navarro Oliva and co-workers prepared core-shell-structured NNHs by the coaxial electrostatic spinning technique using an Fe 3 O 4 solution as the core layer and a PVDF polymer solution as the shell layer. As shown in Figure 4B, TEM images showed that the NPs were uniformly dispersed inside the fibers without agglomeration [84]. Combining both electrospinning and electrospraying to prepare NNHs is also a convenient method.…”
Section: Formation Of Nnhs In the Single-step Processmentioning
confidence: 95%
“…The CA films with high electrostatic safety suitable for MEMS microinitiators were then obtained via high-temperature carbonization and in situ azide processes. When compared to the traditional electrospinning technology, the coaxial electrospinning process can produce materials that cannot be electrospun individually into new nanofibers, as well as core–shell nanofibers. This core–shell structure allows a carbon shell to be wrapped around the fibers’ surface, providing double protection for the CA and reducing its electrostatic sensitivity even further. Furthermore, the CA-based film can successfully detonate secondary explosives if the energy and sensitivity requirements are met, effectively alleviating the problem of powder samples being difficult to process and form.…”
Section: Introductionmentioning
confidence: 99%